PrEP knowledge and perceptions among women living in North Carolina public housing communities - Lauren M. Hill; Olivia Allison; Oluwamuyiwa Adeniran; Marcella Jones; Suur Ayangeakaa; Tonya Stancil; K. Jean Phillips-Weiner; Alexandra F. Lightfoot; Mehri S. McKellar; Carol E. Golin (PLoS ONE, 2025)
Women in low-income communities are disproportionately affected by HIV yet have been largely left out of efforts to raise awareness about pre-exposure prophylaxis (PrEP). To inform future awareness campaigns, we assessed women’s current knowledge of and attitudes toward PrEP. We surveyed 184 women living in public housing communities in North Carolina regarding PrEP knowledge, attitudes, and perceived norms, as well as reported HIV-associated factors and perceived HIV acquisition chances. 38 women participated in eight focus group discussions (FGDs) addressing personal and community PrEP perceptions. Survey participants were 46 years old on average, and 86% identified as Black/African American. Only 35% had heard of PrEP, yet, after being told what it was, 61% said they probably or definitely would take PrEP in the next 6 months. Most women believed that if they decided to take PrEP, their partner (72%) or their family (66%) would approve. When asked about the importance of factors influencing their interest in PrEP, women most frequently rated possible side effects as important or very important (76%), followed by cost considerations (67% for cost of PrEP, 74% for cost of clinic visits and labs). In the FGDs, women had limited PrEP knowledge, but several had heard of PrEP from television commercials, which gave them the impression that PrEP was only for men. Women were concerned about potential side effects, interactions with other medications, safety during pregnancy, and the burden of daily dosing. Most FGD participants expressed generally positive attitudes toward PrEP, but some thought other women would be uninterested due to low perceived chances of HIV acquisition. Overall, these results suggest that while few women had previously heard of PrEP, most were interested in PrEP after receiving information about it and perceived positive community attitudes toward PrEP. Our findings indicate the importance of community-based PrEP communication that speaks to cisgender women, provides information on side effects, and offers destigmatized messaging regarding reasons for HIV prevention for women to consider.